How do affected interests support global democracy? - Andrić, Vuko (Journal of global ethics, 2017)
In this paper, I critique one way of arguing for global democracy on grounds of affected interests and defend another. A famous argument for global democracy, which I call the Demos-Based Argument, attempts to justify global democracy based on the claim that affected interests vindicate individual claims to democratic participation or representation. I analyze and evaluate the Demos-Based Argument and consider different ways of interpreting and justifying its crucial premise: the Principle of Affected Interests. The result is that the argument fails. One lesson of the discussion of the Demos-Based Argument is that the most promising, though eventually unsuccessful, justification of the Principle of Affected Interests is utilitarian. Given the failure of the Demos-Based Argument, the question suggests itself if there is another way to argue for global democracy on utilitarian grounds. I will outline a promising alternative argument for global democracy, which I call the Direct Argument. Like the Demos-Based Argument, the Direct Argument is based on affected interests and ultimately on utilitarianism, but unlike the former, the Direct Argument avoids the detour over stating a criterion for individual claims to democratic participation and representation.